The Role of Liquidity Management in Enhancing Corporate Financial Stability: a Systematic Literature Review on Cash Reserves and Marketable Securities Strategies - Fangandrododo Ndruru (PRODUCTIVITY: Journal of Integrated Business, Management, and Accounting Research, 2025)
This study explores the role of liquidity management in enhancing corporate financial stability, focusing on cash reserves and tradable securities strategies. Effective liquidity management helps companies manage financial risks and take advantage of investment opportunities, especially in the face of economic uncertainty. This study uses a systematic literature review approach to analyze the relationship between liquidity, cash reserves, and tradable securities. Cash reserves serve as a financial buffer to deal with cash flow fluctuations and reduce dependence on external funding. Meanwhile, tradable securities provide additional financial flexibility through quick access to liquidity. This study shows that companies that manage their liquidity well tend to have better financial stability, reduce bankruptcy risk, and increase investor confidence. This study also identifies research gaps, including the effects of financial technology and macroeconomic conditions on liquidity strategies. The practical and theoretical implications of this study provide guidance for companies to manage their liquidity more effectively, ensure business continuity, and support long-term growth